Estudio sobre manejo de suelos y calidad de aguas en la zona sur de San Bosco - Santa Barbara, Heredia (ING) - Villalobos, Cecilia (1994)
Undue soil use without considering its productive potential and the ignorance or lack of interest of producers to implant soil conservation and management practices, are causing serious degradation problems on agricultural land.Considering that the Universidad National develops a program to recover the Río Segundo Basin, it was decided to carry out a diagnostic that shows the problems related with the soil and water use and management, in 17 small farms in San Bosco of Santa Bárbara, Heredia.It was found that soils of the zone present suitable physical and chemical characteristics for agricultural production. However its present management system as well as relief and slope factors are causing soil losses.It was determined that the chemical water quality is acceptable but it is biologically inacceptable. The soil characteristics and the irregular topography determine the need to establish soil management systems which protect its agricultural potential, especially when an irrigation project begins in this zone.